Konstruksi Naratif Pemberitaan Gus Miftah: Analisis Semiotika di Republika.co.id - Amelia, Rara; Marini; Salas, Hagi Julio (El Madani: Jurnal Dakwah dan Komunikasi Islam, 2025)
The development of information technology has transformed how online media shape public opinion and social meaning construction. This study analyzes news coverage of Gus Miftah's case of insulting an iced tea vendor on Republika.co.id using Roland Barthes' semiotic approach. The research aims to reveal how online media form social narratives and myths through religious figure coverage. The method uses qualitative analysis focusing on denotative, connotative, and mythological meanings in three Republika.co.id news articles published on December 3-5, 2024. The findings show that media construct Gus Miftah's image as a controversial figure who does not meet dakwah ethics standards. At the denotative level, all three news articles agree on the factual events. The connotative level reveals the coarseness and impoliteness of religious figures. The mythological level reinforces discourse on the importance of religious figures' moral integrity and the sacredness of the "Gus" title. Social media functions as a moral court that tests the authenticity of religious identity. This research contributes to understanding media's role in constructing social meaning related to religious figures in the digital era.